RESISTANCE TRAINING FOR YOUTH: MYTHS AND FACTS - Dragan Radovanović; Aleksandar Ignjatović (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
Using resistance training with the aim of developing muscle strength among youth is still a matter of debate and often receives severe criticism. Previous research, which has not noted an increase in muscle strength, led to the conclusion that resistance training is ineffective among youth. However, the results of numerous more recent studies which have closely followed the published statements and recommendations obtained by leading global professional and health organizations, indicate that if carried out properly, resistance training among youth can have very positive results. In addition to its positive influence on muscle strength and endurance, as well as the potential increase in the success rate of motor performance, regular resistance training can result in the improvement of body composition, increased bone mineral density, an improvement in cardiorespiratory fitness, as well as its influence on one's psychological well-being. The most commonly used types of load for resistance training include free weights and weight machines, which can have standard dimensions, but are also specially designed for younger people. It is also often the case that these training programs consist of body weight exercises, exercises with a medicine ball, expanders and elastic bands. Current findings from well-organized and monitored studies involving samples of youth indicated a very small possibility of injury during resistance training, provided that all the training recommendations for the given age group are adhered to.